Comparison of different twin-screw extraction conditions for the production of arabinoxylans. (13th February 2015) - Jacquemin, Leslie; Mogni, Assad; Zeitoun, Rawan; Guinot, Cécile; Sablayrolles, Caroline; Saulnier, Luc; Pontalier, Pierre-Yves
Highlights: Evaluation of a pilot scale arabinoxylan production process. Influence of different alkaline extraction conditions. Influence of two different destarching methods. Study of different combinations of operation stages for recovery of arabinoxylans. Abstract: The aim of this article is to compare two different sets of optimal conditions for twin-screw extraction of xylans and define their influence on the purification steps, combining ultrafiltration and industrial chromatography. Two xylan extracts were obtained by twin-screw extrusion of straw and bran. Condition 1 used a high straw/bran ratio (equal to 6) and high sodium hydroxide content, and condition 2 used a lower straw/bran ratio (equal to 2) and low sodium hydroxide content. Arabinoxylan extraction yields are slightly higher for conditions with low straw content (5.1% versus 4.4%). Nevertheless, these recovery yields remain between 9% and 10%. Ultrafiltration is as efficient as evaporation for polysaccharide concentration, with lower energy consumption, but also demineralizes the solution. The combination of ultrafiltration and chromatography gives partial purification of the extract with a final arabinoxylan purity ranging from 16% to 26%. This is slightly higher than by direct precipitation, but limited because all the large molecules such as proteins and lignins were retained by ultrafiltration.